Normatywne ujęcia antyprokreacji - Tokarczyk, Roman (Wydawnictwo Naukowe UAM, 2000)
From the dawn of history, different ways of preventing human birth have belonged tomajor normative problems. From the normative viewpoint, this prevention is usually called birth control that embraces all the relevant biological, medical, chemical and other methods. From the medical standpoint, birth control is based mainly on three methods: contraception, contra-gestation and abortion. Already primitive peoples practiced their own methods of preventing pregnancy: avoidance of intercourse at certain periods and various means of prevention: magic, medical, chemical, mechanical and surgical. One of the most controversial problems of anti-procreation is abortion. The practice of abortion is presumaably as old as human history. Three solutions compete in the normative regulations an abortion: ban, admissibility under strictly defined circumstances, and full admissibility. In legal regulations concerning abortion three models can be distinguished: either giving preference to the protecition of the pregnant woman’s interests, or the interests of the foetus, or seeking compromise between those two adverse interests. The Polish law leans towards the third model. Sterilization occupies a separate position in the vast issues of anti-procreation. The moral evalution of and regulations concerning sterilization vary depending on its voluntary or compulsory character, applied to men or women. Speaking in most general terms, anti-procreation in all its manifestations, essentially striving for infertility, is subject to highly diversified assessment and regulations that cannot claim to be universal.
Normative interpretations of antiprocreation